Community-Based Forest Management: Challenges and Opportunities in Tropical Asia - Reyes, Maria Clara; Flores, Josefa; Fernandez, Carlos (Journal of Selvicoltura Asean, 2024)
Community-based forest management (CBFM) has gained prominence as a strategy for sustainable forest governance in tropical Asia. This approach seeks to empower local communities, enhance biodiversity conservation, and improve livelihoods. However, the implementation of CBFM faces numerous challenges that can hinder its effectiveness. This research aims to identify the key challenges and opportunities associated with CBFM in tropical Asia. The study seeks to provide insights into the factors influencing successful implementation and to highlight best practices that can enhance community engagement in forest management. A mixed-methods approach was employed, combining qualitative interviews with community members, local officials, and NGOs, along with quantitative surveys of forest management practices. Case studies from selected countries in tropical Asia were analyzed to identify common themes and variations in CBFM implementation. Findings reveal that while CBFM has the potential to improve forest sustainability and empower communities, challenges such as inadequate capacity, lack of financial resources, and conflicting interests among stakeholders persist. Opportunities for enhancing CBFM include strengthening local governance structures, improving access to technology, and fostering partnerships with NGOs and government agencies. The study concludes that addressing the challenges of CBFM is essential for its success in tropical Asia. By leveraging the identified opportunities, stakeholders can enhance community participation and promote sustainable forest management. This research underscores the importance of an integrated approach that combines local knowledge with external support to achieve effective CBFM outcomes.